CYTOTOXIC AND ANTIOXIDANT ACTIVITIES OF SECONDARY METABOLITES FROM PULICARIA UNDULATA - Hussien, Taha A.; El-toumy, Sayed A.; Hassan, Hossam M.; Hetta, Mona H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To evaluate the in vitro cytotoxicity, antioxidant activities and structure-activity relationship of secondary metabolites isolated from Pulicaria undulata. Methods: The methylene chloride-methanol (1:1) extract of the air-dried aerial parts of Pulicaria undulata was fractionated and separated to obtain the isolated compounds by different chromatographic techniques. Structures of the isolated compounds were determined on the basis of the extensive spectroscopic analysis, including 1D and 2D NMR and compared with the literature data. The crude extract and the isolated compounds were evaluated for in vitro antioxidant activity using the 2,2 diphenyl dipicryl hydrazine (DPPH) method and cytotoxic assay using human breast cancer (MCF-7) and hepatoma (Hep G2) cell line. Results: Nine secondary metabolites were isolated from Pulicaria undulata in this study. Of which two terpenoidal compounds; 8-epi-ivalbin and 11Î², 13-dihydro-4H-xanthalongin 4-O-Î²-D-glucopyranoside firstly isolated from the genus pulicaria and three flavonoids; eupatolitin, 6-methoxykaempferol, and patulitrin firstly isolated from P. undulata. 6-methoxykaempferol (IC50 2.3 Âµg/ml) showed the most potent antioxidant activity. The highest cytotoxic effect against MCF-7 and Hep G2 cells was obtained with eupatolitin (IC50 27.6 and 23.5 Âµg/ml) respectively. The structure-activity relationship was also examined and the findings presented here showed that 3, 5, 7, 4' and 3, 5, 4', 5'-hydroxy flavonoids were potent antioxidant and has cytotoxic activity. Conclusion: Pulicaria undulata is a promising medicinal plant, and our study tends to support the therapeutic value of this plant as antioxidant drug and in the treatment of cancer.